2018
DOI: 10.1002/da.22863
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of trajectories of suicidal ideation and depression symptoms: Evidence from a randomized controlled trial

Abstract: Background: Depression is a risk factor for suicidal ideation. However, suicidal ideation can occur in the absence of depression and treating depression may not reduce suicidal thinking. This study tested whether trajectories of suicidal thinking are concordant with trajectories of depressive symptoms and sought to identify factors associated with these trajectories. Methods:Participants were community-based Australian adults (N = 418, 77% female) enrolled in a randomized controlled trial evaluating the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
31
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 54 publications
6
31
2
Order By: Relevance
“…However, many who ultimately die by suicide have not received mental health care in their last year (e.g., Miller & Druss, 2001), limiting the impact clinical interventions for suicide can have. Further, suicide is the result of a variety of biological, genetic, social, cultural, psychological, and behavioral factors, which are not all addressed by clinical interventions (e.g., Batterham et al, 2019; De Leo, 2004; Iyengar et al, 2018; Michel et al, 2017; Qin et al, 2003; Turecki et al, 2019). As such, suicide prevention requires public health approaches to reduce risk in the whole population (Caine, 2013; David‐Ferdon et al, 2016; Goldsmith et al, 2002; Knox et al, 2004; Roof et al, 2016; Sanddal et al, 2003; U.S. Public Health Service, 1999; 2001; Yip, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, many who ultimately die by suicide have not received mental health care in their last year (e.g., Miller & Druss, 2001), limiting the impact clinical interventions for suicide can have. Further, suicide is the result of a variety of biological, genetic, social, cultural, psychological, and behavioral factors, which are not all addressed by clinical interventions (e.g., Batterham et al, 2019; De Leo, 2004; Iyengar et al, 2018; Michel et al, 2017; Qin et al, 2003; Turecki et al, 2019). As such, suicide prevention requires public health approaches to reduce risk in the whole population (Caine, 2013; David‐Ferdon et al, 2016; Goldsmith et al, 2002; Knox et al, 2004; Roof et al, 2016; Sanddal et al, 2003; U.S. Public Health Service, 1999; 2001; Yip, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In a cohort of depressed outpatients, Batterham et al have identified different types of trajectories of SI and depressive symptoms. The characteristics of class membership were different for the two outcomes (Batterham et al, 2019). Some factors could thus impact changes of SI independently of depression.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, among individuals with treatment-resistant MDD, a recent randomized placebo-controlled trial showed large decreases in depressive symptoms 1, 2, and 7 days administration of ayahuasca (Palhano-Fontes et al, 2019). However, extant research suggests that suicidality can occur independent from depressive symptoms (Brent et al, 2005; Brent, 2010; Brent and Mann, 2010; Dutta et al, 2017; Batterham et al, 2019) and decreases in depressive symptoms are not always associated with decreases in suicidality (Christensen et al, 2013). For instance, compared with placebo, even first-line interventions for depression (i.e., selective serotonin reuptake inhibitors; SSRIs) lead to limited to no decreases in suicidality (intent to treat ES = –0.04–0.20; Näslund et al, 2018).…”
Section: Introductionmentioning
confidence: 99%